Examining Nursing Students’ Perspectives on Cancer through Metaphors in Turkey - Kırca, Kamile; Kaş, Canan (Springer Science and Business Media LLC, 2022)
This study was conducted to reveal the perceptions of cancer through metaphors among second-year nursing students. This study utilized descriptive phenomenology, which is a qualitative research design. In order to reveal the metaphors that each nursing student (n = 65) considered for the concept of "cancer," they were asked to complete the following sentence: "Cancer is like ……, because ……". In analyzing the data, a content analysis approach comprising coding, the identification of themes, and grouping of data according to codes and themes was used. It was found that the nursing students produced 44 different metaphors. With the groupings made from the students' perspectives on cancer, categories of "crime/punishment," "fear/anxiety/pain," "uncertainty," "uncontrollability," and "struggle/hope" were identified. In particular, the students' metaphors of "test," "fight," "unwanted friend," "love," "naughty child," "thief," and "trouble" for the concept of cancer came to the fore. It is recommended to improve clinical education to develop positive attitudes among nursing students toward cancer.
Keywords: Turkey; Cancer; Metaphor; Nursing student; Perspective; Neoplasms; Metaphor; Humans; Students, Nursing; Qualitative Research; 4. Education; 3. Good health